Amino Acid Digestibility of Feed Ingredients in Cecectomized Adult Roosters - Leme, B. B. [UNESP]; Sakomura, N. [UNESP]; Viana, G. S. [UNESP]; Soares, L. [UNESP]; Melare, M. C. [UNESP]; Oliveira, M. J. K. [UNESP]; Mansano, C. F. M. [UNESP] (Facta-fundacio Arnco Ciencia Tecnologia Avicolas, 2019)
A digestibility assay was conducted in order to determine the digestibility coefficients (DC) of amino acids of feed ingredients in cecectomized adult roosters. In total 48 cecectomized adult roosters were used to assess the coefficient of digestibility of 7 ingredients: corn, soybean meal, soybean concentrate, corn gluten meal, wheat bran, peanut meal, and feather meal. Each ingredient was replicated six times and a group of 6 rooster was used to measure endogenous amino acid losses. After 48 hours of fasting, the roosters were tube fed 20g of ingredients tested twice during a day. At 12 hour-intervals excreta and endogenous losses were collected and immediately freeze-dried for further chemical analysis. At the end of the assay, excreta were weighed and samples of ingredients, excreta, and endogenous losses were pooled and analysed for dry matter, nitrogen and amino acid content. The coefficients of indispensable amino acids for the most feed ingredients assessed in the current research were similar to published literature like AMINODat (R) 5.0 and the 41' edition of the Brazilian Tables for Poultry and Swine, except feather meal, in which only digestible Trp and Thr content were similar to literature. Particularly, the coefficients for some amino acids like Arg and Gly exhibited large discrepancies from literature in almost all the feed ingredients assessed herein. In general, using cecectomized adult roosters proved to be a reliable technique to assess the digestibility of feed ingredients used in poultry diets.
Keywords: Cecectomized; digestibe amino acids; poultry